Perceptions of leadership qualities among journalism students with different levels of academic performance - Shtyrev, Mikhail Mikhailovich; Bashkin, Evgenii Bronislavovich (Психолог, 2025)
The subject of this article's research is the perceptions of journalism students regarding leadership qualities depending on their academic performance. The relevance of the topic is due to the necessity of understanding how students perceive qualities important for effective leadership and how this perception is related to their academic achievement. The significance of this topic is linked to the formation of primary social roles and the development of personal qualities in the student environment, which directly influence professional adaptation. The aim of the research is to identify differences in the views of students with high and low academic performance on the importance of specific leadership qualities and their perceptions of what a leader should be. The study is focused on refining strategies for developing the leadership potential of students within educational programs and student self-governance. A comprehensive approach was used in the research, including quantitative (surveys, Mann-Whitney U test) and qualitative (in-depth interviews using the STAR model) methods of analysis. The scientific novelty of the research lies in the empirical confirmation of the relationship between the academic performance of journalism students and their perceptions of leadership qualities. The study identified a list of the most significant leadership qualities, such as organizational thinking, sociability, result-orientation, persuasiveness, creativity, self-control, and empathy, which students perceive as essential for a successful leader. It was found that students with low academic performance often highly value pragmatic qualities of a leader aimed at achieving specific results. In contrast, students with high academic performance place greater importance on social and moral aspects of leadership, including empathy and patriotism. The results of the study open up prospects for the targeted development of adaptive educational strategies that foster the formation of leadership qualities in students, taking into account their individual characteristics and academic achievements.